A Possible Early Biomarker for Bicuspid Aortopathy: Circulating Transforming Growth Factor Beta-1 to Soluble Endoglin Ratio - Forte, Amalia; Bancone, Ciro; Cobellis, Gilda; Buonocore, Marianna; Santarpino, Giuseppe; Fischlein, Theodor J.M.; Cipollaro, Marilena; De Feo, Marisa; Della Corte, Alessandro (Circulation research, 2017)
RATIONALE:The pathogenesis of bicuspid aortic valve (BAV)-associated aortopathy is poorly understood and no prognostic biomarker is currently available. OBJECTIVE:We aimed to identify putative circulating biomarkers pathogenetically and prognostically linked to bicuspid aortopathy. METHODS AND RESULTS:By RT-PCR, we evaluated gene expression variations (versus normal aorta) of transforming growth factor-beta1 (TGF-β1), connective tissue growth factor (CTGF), matrix metalloproteinase-2 (MMP-2), MMP-14, endoglin (ENG) and superoxide dismutase 3 (SOD3) in ascending aorta samples from 50 tricuspid and 70 BAV patients undergoing surgery for aortic stenosis (aorta diameter ≤45mmBAVnon-dil or >45mmBAVdil). Expression changes of the TGF-β1 active dimer and ENG were analysed also by Western blot in ascending aorta samples from other 10 TAV, 10 BAVnon-dil and 10 BAVdil patients. The serum concentration of study targets was assessed through ELISA and the ratio of serum TGF-β1 to ENG (T/E) was evaluated. All BAVnon-dil patients underwent follow-up echocardiography to assess aortic growth rate. In BAVnon-dil patients, TGF-β1 and MMP-2 gene expression increased significantly whereas MMP-14 and ENG expression decreased versus controls. Expression changes were confirmed at protein level for TGF-β1 and ENG. TGF-β1 serum concentration significantly decreased in TAV and BAVnon-dil patients versus healthy subjects. ENG serum concentration decreased in all patients, more markedly in BAVdil. A significant increase of the T/E ratio versus healthy subjects was unique of BAV patients. In BAVnon-dil patients, a T/E ≥9 was independently associated in multivariable analysis with higher MMP-2 and lower SOD3 gene expression, independent of age and aortic diameter. A significant correlation was observed between baseline T/E ratio and aortic diameter growth rate in BAVnon-dil patients (r=0.66, p<0.001). CONCLUSIONS:The novel evidence of a possible value of the T/E ratio as a biomarker of BAV aortopathy was presentedfurther validation studies are warranted.